Сейсмическое действие взрыва в горных породах - Кузьменко А. А. Анатолий Александрович; Воробьев В. Д. Виктор Данилович; Денисюк И. И. Иван Иванович; Дауетас А. А. Андрюс Аугустович (Москва, Недра, 1990)
Авторы указаны на обороте титульного листа.